Construção e automação de plataforma robótica móvel mediante o uso algoritmo fuzzy maps cognitive - Okuyama, Thomas Massaru (2015)
This paper presents a proposal for autonomous navigation control by applying Fuzzy Cognitive Maps on an open source platform for low cost Arduino. Fuzzy Cognitive Maps is an intelligent computational technique that has low computational cost. Thus, it is possible to embark with little memory and processing resources. Construction details and the algorithm implemented on a robotic platform are also contemplated.